Fragmentos da moral cristã no cinema de horror de José Mojica Marins - Couto, Giancarlo Backes (2020)
This study attempts to investigate Christian morality in José Mojica Marin’s horror cinema. Our starting question was: in which aspect does the director’s oeuvre carry elements of Christian morality? At which points of the movies are these mores reaffirmed and when are they denied? The starting hypothesis here is that there is an extremely complex and ambiguous relationship with morality, which escapes the mere prerogative of whether Mojica would attack it or indirectly reaffirm it. In order to work with the subject, some main aspects were chosen for discussion, as well as fragments in the director’s oeuvre that deal with the subject. As such, this work was guided by the examination of the relationships between purity and impurity, as well as between blasphemy and the baroque within the filmmaker’s work, relating said concepts both with the movies under discussion and with other works of art that contain them. The methodology employed works in two fashions: first, by combining the concepts of “fragment” and “dialectical image” in Benjamin (1984; 2012; 2017) and, then, by approaching the mentalities (SORLIN, 1985) that emerge from these images. Besides the aforementioned general goal, this study also had specific goals, to wit: examining the content and form of the objects, investigating how specific aspects of Christian morality present themselves; questioning the way in which the object relates to its time, as well as how it carries reminiscences from other historical periods; comparing fragments in Mojica’s film work with other works of art, both in Cinema and elsewhere, so as to understand similarities and differences in the establishment of these works and their relationships with their respective historical periods and Christian morality itself; and understanding the relationship of the object with the society that produced it through the mentalities found in the fragments. Each chapter, in view of the investigation of different aspects, was supported by different sources of theory. In examining the purity/impurity dichotomy, the concept of stain in Ricoeur (1982) was employed, along with the relations between purity and impurity and between order and disorder in Douglas (2014), relating said concepts within horror (CARROLL, 1999). In regards to blasphemy, Nash (2007) and Pieroni (2000; 2002) were the main authors used. When analyzing the baroque, Bataille’s concepts of violence and erotica (2014) were especially used. The conclusions in this study discuss the way in which Christian morality changed over time, appearing in different ways in different works of art. In the films of José Mojica Marins, said aspects of that morality are at times reaffirmed, and other times rejected.